Factors that affecting the employee engagement among employees at UiTM Holdings Sdn Bhd / Nurul Asna Mukhtar and Noor Emilia Ahmad Murad - Mukhtar, Nurul Asna; Ahmad Murad, Noor Emilia (Faculty of Business and Management, 2016)
The purpose of this research is to identify the level of the employee engagement of employees at UiTM Holdings. The dependent variable is employee engagement and independent variables are commitment, meaningfulness work, discretionary effort, leadership, and work environment. This research is being conducted at UiTM Holdings Sdn.Bhd. In completing this research, about 50 questionnaires have been distributed to the respondents. The respondents are included all the staff in UiTM Holdings Sdn Bhd. In order to get the result for this result, the researcher has used SPSS program to analyze data from the information gathered. To analyze the data, the researcher has been used Reliability Analysis, Frequency Distribution, Descriptive Statistic, and Regression Analysis by using SPSS Program. Form the findings, the researcher indicates that the most of the respondents agree that the commitment of the employee is the factor that contributes the most and has highest relationship with employee engagement.